Consent when Linking Survey Data with Administrative Records: The Role of the Interviewer - Julie M. Korbmacher; Mathis Schröder (Survey Research Methods, 2013)
Linking survey data with administrative records is becoming more common in the social sciences in recent years. Regulatory frameworks require the respondent's consent to this procedure in most cases. Similar to non-response, non-consent may lead to selective samples and could pose a problem when using the combined data for analyses. Thus investigating the selectivity and the determinants of the consent decision is important in order to find ways to reduce non-consent. Adapting the survey participation model by Groves and Couper (1998), this paper identifies different areas influencing the respondents' willingness to consent. In addition to control variables at the individual and household level, two further areas of interest are included: the interview situation and the characteristics of the interviewer. A multilevel approach highlights the importance of the interviewer for the consent decision: the empty model shows an intra-class correlation of 55%, which can be reduced to 35% in a full model including interviewer variables. An additional analysis including measures of interviewer performance shows that there are further unobserved interviewer characteristics that influence the respondent's consent decision. The results suggest that although respondent and household characteristics are important for the consent decision, a large part of the variation in the data is explained by the interviewers. This finding stresses the importance of the interviewers not only as an integral part in data collection efforts, but also as the direct link to gain a respondent's consent for linking survey data with administrative records.
Keywords: 300; record linkage; interviewers; Statistische Methode; Interview; Daten